Ultrasound-guided liver biopsy using a Tru-cut needle: a safe and effective diagnostic technique in bovine practice (FAVE Sección Ciencias Veterinarias, 2025)
Liver biopsy sampling can be a valuable diagnostic tool for several deseases in cattle. Although there may be some apprehension for using the technique, the procedure has a low risk of adverse consequences when used correctly. The use of proper biopsy site preparation and technique reduces the risk of complications while optimizing the probability of obtaining a sample large enough for evaluation. This work demonstrates that the use of tru-cut needle guided by ultrasonography is an effective and safe for hepatic biopsy collected diagnostic aid maneuver in the bovine clinic.
Keywords: liver biopsy; cattle; bovine medicine; hepatic damage